1974
DOI: 10.1038/bjc.1974.63
|View full text |Cite
|
Sign up to set email alerts
|

Survival Rates of Lung Cancer According to Histological Type

Abstract: Summary.-The post-operative survival in 554 lung carcinomata, classified according to the histological type, was calculated by the actuarial method. On the whole, squamous cell carcinoma was the most favourable and anaplastic small cell carcinoma the least favourable lesion. However, in tumours smaller than 4 cm, confined to the lung and with negative lymph nodes (stage I), small cell carcinoma had the highest percentage of 5 year survivors, followed by large cell carcinoma, squamous cell carcinoma and adenoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…In effect, the data demonstrate the need for only three symptom status categories: I (Zubrod 0-I), I1 (2), and I11 (3)(4). The data did not suggest that information was lost by employing the simpler Zubrod system.…”
Section: Discussio~mentioning
confidence: 75%
“…In effect, the data demonstrate the need for only three symptom status categories: I (Zubrod 0-I), I1 (2), and I11 (3)(4). The data did not suggest that information was lost by employing the simpler Zubrod system.…”
Section: Discussio~mentioning
confidence: 75%
“…The lung cancer survival rate shows a difference by histological type, with NSCLC having a better prognosis compared to SCLC [ 19 ]. However, the staging of a tumor is the strongest determinant factor of lung cancer survival.…”
Section: Discussionmentioning
confidence: 99%
“…However, routine use of these techniques has, so far, been limited and the light microscopic pattern still remains the principal criterion for pathological diagnosis and therapy planning (Sobin, 1991). This was well recognized when, in 1967, a WHO classification (Kreyberg et al, 1967) was suggested in order to distinguish morphological categories of tumours corresponding to different types of clinical behaviour (Kern et al, 1968;Campobasso et al, 1974). This classification was updated in 1981 (WHO, 1981) because of the need for a better reproducibility of typing, using stricter criteria.…”
mentioning
confidence: 99%
“…The same material, classified according to the 1967 WHO criteria under the direction of one of us (O.C. ), had been used in previous studies on clinical-pathological correlations in lung cancer (Campobasso et al, 1974(Campobasso et al, ,1989.…”
mentioning
confidence: 99%
See 1 more Smart Citation